Efficacy of Bisphosphonates for the Treatment of Osteoporosis in Patients with Multiple Sclerosis - İlke Coşkun Benlidayı; Sibel Başaran; Ahmet Evlice; Miray Erdem; Meltem Demirkıran (Türk Osteoporoz Dergisi)
Objective: The aim of this study was to evaluate the effectiveness of bisphosphonates in osteoporotic patients with multiple sclerosis. Materials and Methods: Patients with multiple sclerosis, who were started on treatment with a diagnosis of osteoporosis, at the Department of Physical Medicine and Rehabilitation, Faculty of Medicine Çukurova University, between January 2011 and January 2014, were included in this study. Patients were allocated into control (calcium-vitamin D alone) and active treatment (calcium-vitamin D and bisphosphonate) groups according to their medications. Response to the 12-month treatment in terms of bone mineral density (BMD) values and biological marker levels were evaluated, both within and between groups. Results: The study group consisted of 29 patients (14 controls and 15 active treatment). Evaluation performed within each group revealed no significant difference between baseline and post-treatment values of BMD and biological markers in controls. However, regarding the active treatment group, a significant increase in L1-L4 T-score and 25(OH)D was detected. When delta values were taken into account, comparison between groups revealed no significant difference in terms of BMD and biological marker levels. Conclusion: The effect of calcium-vitamin D alone on BMD and biologic markers was similar to that of calcium-vitamin D and bisphosphonate combination, in multiple sclerosis patients with osteoporosis. However, prospective, randomized, controlled studies are required on this issue. (Turkish Journal of Osteoporosis 2015;21: 53-7)